Effect of laparoscopic ovarian cystectomy on ovarian reserve in benign ovarian cysts - Madeti Usharani Sireesha; Thyagaraju Chitra; Murali Subbaiah; Hanumanthappa Nandeesha (Wolters Kluwer Medknow Publications, 2021)
Background: Laparoscopic cystectomy is one of the common modes of treatment for benign ovarian cysts. The data related to the effect of cystectomy on ovarian reserve are limited. Aim: The aim of this study was to investigate the effect of laparoscopic ovarian cystectomy on anti-Mullerian hormone (AMH) levels in benign ovarian cysts. Settings and Design: It was a prospective clinical study conducted in a tertiary care hospital from March 2017 to August 2018. Materials and Methods: Seventy-two benign ovarian cyst patients who were admitted for cystectomy were enrolled in the study. Serum AMH levels were estimated in all the patients at baseline, 1 week, and 3 months after cystectomy. Statistical Analysis: Paired t-test was used to assess the differences in AMH levels before and after laparoscopic cystectomy. Results: AMH was significantly reduced after 1 week (P < 0.05) and 3 months (P < 0.05) of cystectomy compared to preoperative levels in both endometriotic and nonendometriotic cysts. The percentage of reduction in the AMH values measured on the 7th postoperative day was found to be greater with endometriotic cysts (54%) followed by mucinous cystadenoma (32%). On day 90, greater recoveries of the AMH values to the baseline AMH levels were observed with cystic teratoma (83% of the baseline AMH levels). Conclusions: Laparoscopic ovarian cystectomy reduces AMH levels immediately after surgery, and improvement in AMH level was observed after 3 months.